2021
DOI: 10.3386/w28381
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Regulation on Innovation

Abstract: Does regulation affect the pace and nature of innovation and if so, by how much? We build a tractable and quantifiable endogenous growth model with size-contingent regulations. We apply this to population administrative firm panel data from France, where many labor regulations apply to firms with 50 or more employees. Nonparametrically, we find that there is a sharp fall in the fraction of innovating firms just to the left of the regulatory threshold. Further, a dynamic analysis shows a sharp reduction in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Although there is a large literature examining the potential effects of regulation of labor on economic outcomes, studies on the impact of labor laws on innovation are limited (Aghion et al , 2019).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Although there is a large literature examining the potential effects of regulation of labor on economic outcomes, studies on the impact of labor laws on innovation are limited (Aghion et al , 2019).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…This interplay between new technologies and firm capabilities determines both the rate of adoption of technologies, but also their productivity effects. Firms are therefore reluctant to make the necessary investment owing to the burden of red tape (see Aghion et al, 2021, for a review and an example of the negative impact of regulations on innovation).…”
Section: Conditions For a Full Productivity Benefit From Ict And Digitalisationmentioning
confidence: 99%
“…From the above, it appears that government intervention to address market failures affects competition (Friske and Zachary 2017), entrepreneurship (Chambers and Munemo 2017), investment (Eifert 2009). Through competition, regulation affects innovation by firms (Aghion et al 2005(Aghion et al , 2021. Therefore, using an endogenous growth theoretical framework, Blind (2016) states that economic regulations can exert competitive pressure on firms, and in fine impact firm innovation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These theories have thus interpreted comparative growth between economies without considering the "institutional quality" factor, and thus without considering the "business regulation" factor. However, it has previously been shown that business regulatory reforms affect the ability of states to achieve such accumulation in physical and human capital (Chambers and Munemo 2017;Eifert 2009;Branstetter et al 2014), and technological innovation (Aghion et al 2005(Aghion et al , 2021Blind 2016). But it was from the work of North and Thomas (1973) that comparative growth of economies began to be explained by differences in institutional quality in endogenous growth theories.…”
Section: Theoretical Backgroundmentioning
confidence: 99%